Engaging Children in Music-Making: A Feasibility Study Using Disabled Musicians as Mentors in Primary Schools - Eamonn McCarron; Erica Curran; Paul McQueen; Roy McConkey (MDPI AG, 2023)
The place of music in the school curriculum is under increasing threat, yet this is contrary to the growing evidence base of music's value to pupils' social and psychological development. A contributory factor is that many teachers report a lack of training, skill, confidence, or resources for excluding music in their classroom. An innovative project used young adults with disabilities as music mentors to improve children's access to creative music-making, while also providing non-threatening models to the children's teachers and providing them practical tools to embed music in their classrooms. An evaluation was undertaken of the project's impact. Eight classes from four schools in a city with high levels of social deprivation received 16 hours of music sessions over a four-week period, usually in the form of a four-hour workshop. Information was gathered from 171 children, the parents of 54 pupils; 8 class teachers; and 2 head teachers. The pupils' knowledge and appreciation of music showed significant improvements and their enthusiasm for music making had increased, which parents also confirmed. The teachers and head teachers identified five ways in which they had gained from Project Sparks with an increased appreciation of the potential value of music in the school curriculum. Further research is needed to identify how innovative projects can be sustained and extended to many more teachers and schools.